Cross‐shelf transport, oxygen depletion, and nitrate release within a forming mesoscale eddy in the eastern Indian Ocean. (11th November 2015) - Waite, Anya M.; Beckley, Lynnath E.; Guidi, Lionel; Landrum, Jason P.; Holliday, David; Montoya, Joseph; Paterson, Harriet; Feng, Ming; Thompson, Peter A.; Raes, Eric J.
Abstract: Mesoscale eddies may drive a significant component of cross‐shelf transport important in the ecology of shelf ecosystems and adjacent boundary currents. The Leeuwin Current in the eastern Indian Ocean becomes unstable in the austral autumn triggering the formation of eddies. We hypothesized that eddy formation represented the major driver of cross‐shelf transport during the autumn. Acoustic Doppler Current Profiler profiles confirmed periodic offshore movement of ∼2 Sv of shelf waters into the forming eddy from the shelf, carrying a load of organic particles (>0.06 mm). The gap between inflow and outflow then closed, such that the eddy became isolated from further direct input of shelf waters. Drifter tracks supported an anticyclonic surface flow peaking at the eddy perimeter and decreasing in velocity at the eddy center. Oxygen and nutrient profiles suggested rapid remineralization of nitrate mid‐depth in the isolated water mass as it rotated, with a total drawdown of oxygen of 3.6 mol m −2 to 350 m. Depletion of oxygen, and release of nitrate, occurred on the timescale of ∼1 week. We suggest that N supply and N turnover are rapid in this system, such that nitrate is acting primarily as a regenerated nutrient rather than as a source of new nitrogen. We hypothesize that sources of eddy particulate C and N could include particles sourced from coastal primary producers within ∼500 km such as macrophytes and seagrasses known to produce copious detritus, which is prone to resuspension and offshore transport.